2006
DOI: 10.1080/02652030600723245
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofFusariumtoxin-contaminated wheat and feed intake level on the biotransformation and carry-over of deoxynivalenol in dairy cows

Abstract: An experiment was carried out to examine the effects of feeding Fusarium toxin-contaminated wheat (8.21 mg deoxynivalenol (DON) and 0.09 mg zearalenone (ZON) per kg dry matter) at different feed intake levels on the biotransformation and carry-over of DON in dairy cows. For this purpose, 14 ruminal and duodenal fistulated dairy cows were fed a diet containing 60% concentrate with a wheat portion of 55% (Fusarium toxin-contaminated wheat (mycotoxin period) or control wheat (control period)) and the ration was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 27 publications
4
60
2
1
Order By: Relevance
“…In both periods of the present study, and independent of the concentrate proportion, DOM-1 was the predominant component found in the serum samples of cows fed the Fusarium toxin-contaminated diets. These results are in accordance with Seeling et al [2] who fed a ration with 60% concentrate and 3.9 mg DON/kg DM to 14 fistulated dairy cows over a period of 4 wk and detected DOM-1 concentrations between 4 and 28 ng/mL in the serum, but no unmetabolised DON. Accordingly Prelusky et al [5] found that less than 1% of DON were systemically absorbed in two cows fed a very high single oral dose of 1.9 mg pure DON/ kg BW (920 mg per animal).…”
Section: General Aspects Of Residues In Serum Milk and Bilesupporting
confidence: 95%
See 1 more Smart Citation
“…In both periods of the present study, and independent of the concentrate proportion, DOM-1 was the predominant component found in the serum samples of cows fed the Fusarium toxin-contaminated diets. These results are in accordance with Seeling et al [2] who fed a ration with 60% concentrate and 3.9 mg DON/kg DM to 14 fistulated dairy cows over a period of 4 wk and detected DOM-1 concentrations between 4 and 28 ng/mL in the serum, but no unmetabolised DON. Accordingly Prelusky et al [5] found that less than 1% of DON were systemically absorbed in two cows fed a very high single oral dose of 1.9 mg pure DON/ kg BW (920 mg per animal).…”
Section: General Aspects Of Residues In Serum Milk and Bilesupporting
confidence: 95%
“…The DON concentrations in the diets were, with 4.4 (Myco-30) and 4.6 mg/kg DM (Myco-60; Period 2) and 5.3 mg/kg DM (Period 1), respectively, higher than by Seeling et al [2] and this is reflected in higher DON and DOM-1 concentrations in the serum samples. DOM-1 concentrations were significantly linearly correlated with the DON intake (Fig.…”
Section: General Aspects Of Residues In Serum Milk and Bilementioning
confidence: 53%
“…The intervention reduced wheat intake by . 90 %, and the urinary concentration of fD þ DG was also significantly (88) . This intervention restricted the types of food consumed rather than attempting to reduce the contamination level within the consumed food; thus readers should avoid a direct comparison of this outcome with that of the FB intervention above (82) .…”
Section: Deoxynivalenolmentioning
confidence: 83%
“…DON is mostly biotransformed within the rumen and detected in milk as DON and deepoxy-deoxynivalenol (DOM-1) [20][21][22], whereas T-2 has been detected in the milk without metabolization [23] and metabolized into HT-2, NEO, 4-deacetylneosolaniol, and 4 more unknown metabolites [24]. Metabolites could have different toxic effects than the parent mycotoxin [25,26].…”
Section: Introductionmentioning
confidence: 99%